2021
DOI: 10.3389/fcell.2021.639952
|View full text |Cite|
|
Sign up to set email alerts
|

SARAF and Orai1 Contribute to Endothelial Cell Activation and Angiogenesis

Abstract: Angiogenesis is a multistep process that controls endothelial cells (ECs) functioning to form new blood vessels from preexisting vascular beds. This process is tightly regulated by pro-angiogenic factors, such as vascular endothelial growth factor (VEGF), which promote signaling pathways involving the increase in the intracellular Ca2+ concentration ([Ca2+]i). Recent evidence suggests that store-operated calcium entry (SOCE) might play a role in angiogenesis. However, little is known regarding the role of SARA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 40 publications
2
21
0
1
Order By: Relevance
“…This PM Ca 2+ flux was sensitive to changes in expression of either Orai1 or SARAF, suggesting that binding of SARAF to Orai1 stimulated channel activation [76]. In line with a stimulatory role for SARAF during SOCE activation, Ca 2+ imaging experiments in human endothelial cells showed that RNAi-mediated knockdown of Orai1 or SARAF expression attenuates VEGF-induced Ca 2+ entry [77]. Because Albarran et al had used cells with low expression levels of STIM1, their model suggested that SARAF contributes to Orai1 channel activation independently of STIM1 [76]; however, it is not clear that the contribution of SARAF to Ca 2+ entry in these cells was indeed STIM-independent as it may have involved STIM2, which also mediates SOCE in cells [12] and which is also regulated by SARAF [52].…”
Section: Current Models For Scdi By Sarafmentioning
confidence: 67%
See 3 more Smart Citations
“…This PM Ca 2+ flux was sensitive to changes in expression of either Orai1 or SARAF, suggesting that binding of SARAF to Orai1 stimulated channel activation [76]. In line with a stimulatory role for SARAF during SOCE activation, Ca 2+ imaging experiments in human endothelial cells showed that RNAi-mediated knockdown of Orai1 or SARAF expression attenuates VEGF-induced Ca 2+ entry [77]. Because Albarran et al had used cells with low expression levels of STIM1, their model suggested that SARAF contributes to Orai1 channel activation independently of STIM1 [76]; however, it is not clear that the contribution of SARAF to Ca 2+ entry in these cells was indeed STIM-independent as it may have involved STIM2, which also mediates SOCE in cells [12] and which is also regulated by SARAF [52].…”
Section: Current Models For Scdi By Sarafmentioning
confidence: 67%
“…Therefore, SARAF already physically engages the CRAC channel during channel activation and prior to induction of SCDI. While the functional significance of this early interaction is presently unclear, it may indicate an initial role for SARAF in channel activation [76,77] and raises a critical question regarding how the binding of SARAF to STIM1 ultimately promotes SCDI.…”
Section: Interaction Of Saraf With the Crac Channelmentioning
confidence: 99%
See 2 more Smart Citations
“…This decrease in stem cell population was observed with concentrations of SKF-96365 and YM-58483 that have been used to block the physiological effects of SOC [ 31 , 46 , 47 , 48 , 49 ]. As SKF-96365 and YM-58483 may also target other receptor channels (ROC), GSK-7975A, a more specific inhibitor of Orai-dependent SOCE was used [ 50 , 51 , 52 ]. The fact that GSK-7975A had also significant effects on GSC supports the idea that SOC play a key role in maintaining the GSC pool in GBM as they do in oral/oropharyngeal squamous cell carcinoma cancer stem cells and in liver cancer stem cells [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%